2016
DOI: 10.1371/journal.ppat.1005989
|View full text |Cite
|
Sign up to set email alerts
|

Diversification in the HIV-1 Envelope Hyper-variable Domains V2, V4, and V5 and Higher Probability of Transmitted/Founder Envelope Glycosylation Favor the Development of Heterologous Neutralization Breadth

Abstract: A recent study of plasma neutralization breadth in HIV-1 infected individuals at nine International AIDS Vaccine Initiative (IAVI) sites reported that viral load, HLA-A*03 genotype, and subtype C infection were strongly associated with the development of neutralization breadth. Here, we refine the findings of that study by analyzing the impact of the transmitted/founder (T/F) envelope (Env), early Env diversification, and autologous neutralization on the development of plasma neutralization breadth in 21 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 147 publications
3
49
0
1
Order By: Relevance
“…We observed two distinct evolutionary pathways of viral escape in response to increasing plasma potency and breadth in the twins. By generating chimeric pseudoviruses using the viruses sensitive and resistant to autologous plasma antibodies, we confirmed that the viruses of AIIMS_329 developed resistance to autologous plasma bnAbs by previously established mechanisms (26,27,(42)(43)(44) of V1V2 loop lengthening, an increased number of PNGS, and a loss of critical epitopes like N160. The AIIMS_330 viruses that were resistant to contemporaneous autologous plasma also had longer V2 loops but maintained all epitopes.…”
Section: Discussionsupporting
confidence: 66%
“…We observed two distinct evolutionary pathways of viral escape in response to increasing plasma potency and breadth in the twins. By generating chimeric pseudoviruses using the viruses sensitive and resistant to autologous plasma antibodies, we confirmed that the viruses of AIIMS_329 developed resistance to autologous plasma bnAbs by previously established mechanisms (26,27,(42)(43)(44) of V1V2 loop lengthening, an increased number of PNGS, and a loss of critical epitopes like N160. The AIIMS_330 viruses that were resistant to contemporaneous autologous plasma also had longer V2 loops but maintained all epitopes.…”
Section: Discussionsupporting
confidence: 66%
“…three Envs, while classified as tier 2, are on the more neutralization-sensitive side of the spectrum (23,41). Less consistent neutralization of other, more resistant Envs in the panel was also observed at levels that were clearly distinguishable from those for the negative controls (MLV Env pseudovirus and naive monkey serum; also see Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Neutralization assays. Neutralization against HIV-1 Envs 1086.C K160N and CNE8 was measured using serially diluted, heat-inactivated immunized rhesus macaque serum in the TZM-bl cell assays as previously described, using cells that had been plated 1 day prior to the assay (15,17,30,41,(71)(72)(73)(74)(75)(76)(77)(78)(79)(80). In brief, Env pseudoviruses were generated by transfecting the Env-expressing plasmid DNA alongside the HIV-1 SG3ΔEnv proviral backbone DNA into 293T cells, collecting the supernatant 48 to 72 h later, clarifying it by centrifugation, and storing it in small aliquots at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is one contradictory report which says that a longer V1V2 region is associated with resistance to neutralization (41). Of note, site-specific glycosylation can also influence neutralizing antibody elicitation in a subtype-specific manner (42,43). Although the HIV isolates had increased resistance to bNAbs at the population level, the newly identified bNAb PG16 displayed an extraordinary breadth and potency of neutralization with the chimeric viruses.…”
Section: Discussionmentioning
confidence: 99%